Perspektif Hukum Internasional terhadap Belt and Road Initiative dalam Merespons Perang Dagang China-AS serta Implikasinya bagi Indonesia - Zaenuddin, Amy Cynthia Ramdhani; Limbong, Devina Marsela (Fakultas Hukum Universitas Primagraha, 2025)
The Belt and Road Initiative has become China’s grand strategy to expand its economic and geopolitical influence, while promoting infrastructure development in partner countries like Indonesia. However, amidst the intensifying global competition, U.S. protectionism through high tariffs on China complicates international trade dynamics and poses new challenges for developing countries. This tension directly impacts trade relations, the sustainability of infrastructure projects, and strategic positioning in the region. Therefore, this study aims to analyze the BRI within the framework of international law in the context of the U.S.-China trade war and examine its implications for Indonesia, with the goal of formulating strategic legal recommendations to strengthen Indonesia's position in fair and sustainable international cooperation. This research uses a normative legal approach to analyze international and national legal aspects related to the BRI as China’s response to U.S. protectionist policies. Data is collected from secondary sources, including legal documents, international agreements, trade regulations, and related academic literature. The analysis is conducted qualitatively by examining official WTO documents, the Indonesia-China bilateral agreements, and relevant international trade regulations. The study also analyzes BRI projects in Indonesia through a case study method.